Harmonize rules for digital sequence information benefit-sharing across UN frameworks - Sett, Scarlett; Kress, W. John; Halewood, Michael; Nicholson, David; Nuñez-Vega, Genuar; Faggionato, Davide; Rouard, Mathieu; Jaspars, Marcel; da Silva, Manuela; Prat, Christine; Raposo, Débora S.; Klünker, Irma; et al. (2024)
As multiple UN fora develop parallel rules for sharing benefits from digital sequence information, we urge better coordination. International policymakers should focus on harmonizing new benefit-sharing rules to ensure open access to data, database interoperability, and better benefit sharing outcomes.